Implementation of Children's Naturalistic Loose-parts in Developing Creativity - Tunas, Rosi; Sigit Purnama (Universitas Pendidikan Ganesha, 2023)
The development of early childhood creativity needs to get the right stimulation so that it develops optimally. This study aims to analyze the potential of naturalistic loose-part in developing early childhood creativity and the use of naturalistic loose-part media in developing creativity in children. The method used in this research is a phenomenological qualitative approach that relates to the findings around. The subjects of this study were class teachers and 18 children aged 5-6 years. Data collection techniques by observing, interviewing, and documentation. Data analysis by doing data reduction, presentation, and data verification. The results of this study indicate that the use of naturalistic loose-part media can help develop creativity in early childhood. It is shown by the behavior of active, enthusiastic, and imaginative children participating in teaching and learning activities. Naturalistic loose-part media is demonstrated using wood, stone, twigs, sand, and various objects around it. The results of this study have implications related to children's creativity to encourage teachers to use loose-part objects in learning.